Memahami Dampak Media Sosial terhadap Komunikasi Interpersonal: Pendekatan Teori Komunikasi - Kartini; Elisa Damayanti; Nadya Dwi Ananda; Shafira Putri Zharifa; Nur Aida Nabila; Lia Zuraida; Hafiz Mansyur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The use of social reality construction theory as an addition to social exchange theory is a significant step towards understanding more deeply the impact of social media on interpersonal communication. Social reality construction theory offers a powerful perspective on how social media can shape individuals' perceptions of the reality around them. In this research, the literature method is used with a focus on reviewing and analyzing literature related to the impact of social media on interpersonal communication. The research aims to conduct a critical review of interpersonal communication theory and analyze how this theory has implications for social relationships in the digital era. This research shows that overall, changes in patterns of social relations that arise as a result of social media can be understood through the lens of social exchange theory. Social media provides a platform for information exchange, support, and social interaction, however, the impact is the emergence of dynamics that can sometimes sacrifice the depth and quality of traditional interpersonal relationships.